Production of cellulose from agricultural waste using non-wood chemical pulping method / Leong Soo Kwan and Atikah Kadri - Leong, Soo Kwan; Kadri, Atikah (2006)
Agriculture industry is one of the main industries in Malaysia. This industry has generated large amounts of agrowastes every year, such as banana stem, rice straw, sugarcane bagasse etc. These are regarded as abundant, inexpensive and readily available natural resources for pulping industry. This paper deals with the study of the pulping potentialities of banana stems grown in Malaysia. Banana stems are used as raw material in pulping process to produce cellulose as pulp. The chemical pulping method used in this study is soda pulping, where NaOH is the main chemical used in cooking. Temperature, residence time and dosage of chemical used are the parameters to be manipulated in this non-wood chemical pulping process to get an optimum condition for pulping. A batch reactor was used in this non-wood chemical pulping process. The concentration of NaOH used was varied from 10 - 45% and cooking was at temperatures of 100 - 200°C. The ratio of solid to liquid is set at 1:3 and also the cooking period was varied from 30-210 min. The result shows that the optimum yield of cellulose from this study is at 25%w/w NaOH, cooking at 160°C and for 90 minutes. The yield of pulp is around 30% which is similar to that obtained from oil-palm frond-fiber (Rosli et. al. 2004). The cellulose content from the pulp produced is high which around 90%. The mechanical strength is tested for the paper made from the pulp produced and found that the tensile index is about 41.8 kNm/g, the tear index is 7.38 mNm2 /g and the bursting index is 3.27 kPam2/g. This is comparable to paper Cordeiro et. al. 2004 which used banana pseudo-stem growing in Madeira Island (Portugal) as raw material.